Durability degradation of tunnel-lining-shotcrete exposed to nitric acid: Neutralization and nitrate ion migration. (20th June 2022) - Wang, Jiabin; Mi, Zelong; Zhang, Ting; Wang, Dongjing
Graphical abstract: Highlights: Neutralization of tunnel-lining-shotcrete exposed to N x O y attack from automobile exhaust was investigated. The hydrogen and nitrate ions diffusion, and macroscopic properties of neutral shotcrete were investigated. Neutralization and ions diffusion mechanism were analyzed. Neutralization process of lining-shotcrete divided into three stages. Abstract: The tunnel-lining-shotcrete, in the long highway tunnel, was usually neutralization jeopardized by N x O y attack caused by automobile exhaust. To investigate the neutralization process of lining shotcrete, the nitrate acid solution, simulated N x O y gas, with the pH value of 1, 2 and 3 were used as aggressive medium. Meanwhile, the pH value and nitrate ion content in shotcrete neutralization zone were measured using potentiometry method. After that, the composition and relative content of mineral phases and microstructure were charactered via X-ray diffraction (XRD), thermogravimetric-differential thermal scanning (TG-DSC) and scanning electron microscope (SEM). With increased of the hydrogen ion concentration on nitric acid solution, the pH value and nitrate ion content in neutralization zone were decreased and increased respectively. Meanwhile, those of shotcrete were higher and smaller than those of normal concrete. The loss rate of weight, relative compressive and splitting tensile strength of shotcrete was lower than that of normal concrete as the pH value of 1, while that of shotcrete was higher when the nitric acid pH value of 2 and 3. The neutralization process of nitric acid-exposed-shotcrete was divided into three stages, namely, neutralization reaction, hydration product decomposition, and concrete surface spalling off. The pH value of concrete declined, whereas nitrate ion content in the neutralization zone increased with prolonged immersion time. Moreover, the maximum depth of nitrate ion content was deeper. The yellow-white spongy corrosion product layer formed and covered the specimen surface. Additionally, crisscross macro-cracks appeared on the concrete specimen surface, which caused large amount of aggregates was peeled off.